Titanium gypsum curing agent, preparation method and application

By using titanium gypsum curing agents with components such as excitants, fillers, activated solid waste materials and calcium oxide, the complex composition and high cost of titanium gypsum curing agents are solved, and effective curing of titanium gypsum and improvement of road performance are achieved.

CN119528532AActive Publication Date: 2025-02-28SHANDONG TRAFFIC PLANNING DESIGN INST

Patent Information

Application Number
CN202510103875.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The existing titanium gypsum curing agent has complex composition, complex production process, and large amounts, which leads to increased costs and is difficult to promote and apply on a large scale in projects.

Method used

Provided is a titanium gypsum curing agent, including an exciter, a filler material, an active solid waste material, a calcium oxide and a dispersant, which reduces the water absorption and expansion rate of titanium gypsum through hydration hardening reaction, and enhances its mechanical properties and water stability.

Benefits of technology

It realizes effective curing of titanium gypsum, reduces its porosity, improves water stability and road strength, meets road usage requirements, and significantly reduces engineering costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a titanium gypsum curing agent, a preparation method and application, and belongs to the technical field of road engineering materials. The raw materials comprise, by weight, 30-50 parts of an exciting agent, 10-15 parts of a filling material, 30-50 parts of an active solid waste material, 1-10 parts of calcium oxide, and 2-5 parts of a dispersant; the exciting agent comprises an agent A and an agent B in a mass ratio of 0.025-0.08; the agent A comprises sodium hydroxide and potassium hydroxide; and the agent B comprises composite Portland cement and ordinary Portland cement. The synergistic hydration hardening effect among the solid waste raw materials is fully utilized, the solid waste raw materials and the titanium gypsum can generate the synergistic activation effect through the double salt effect and the tetra-coordination isomorphism effect of silicon, a compound or solid solution with certain strength and stability is formed, harmful substances in the titanium gypsum are physically wrapped, and the titanium gypsum is prepared. The effective curing of harmful substances of the titanium gypsum is realized, and certain road strength is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering materials, and in particular relates to a titanium gypsum curing agent, a preparation method and an application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Titanium gypsum is a waste residue produced by adding lime (or carbide slag) to neutralize a large amount of acidic wastewater when producing titanium dioxide using the sulfuric acid method. Its main component is calcium sulfate dihydrate, and it usually also contains a large amount of impurities such as ferrous sulfate. At present, the treatment method for titanium gypsum is still mainly storage or landfill, which occupies a large amount of land resources and brings certain environmental groundwater, soil and environmental pollution problems.

[0004] Road engineering, especially highway engineering construction, has the characteristic of large material consumption, and has a unique advantage in absorbing large amounts of industrial solid waste. The application of titanium gypsum in road engineering can realize the large-scale application of titanium gypsum, while alleviating the contradiction between land occupation and environmental pollution caused by the storage of titanium gypsum, reducing the cost of engineering construction, and reducing the use of natural fill and sand and gravel materials. However, due to the limitations of the physical and chemical properties of titanium gypsum itself, it is easy to absorb water and swell during long-term use, and cracks will occur when applied to the roadbed; on the other hand, titanium gypsum itself has insufficient water stability, disintegrates when exposed to water, cannot form strength, and is difficult to meet the requirements of road use; furthermore, due to the influence of raw materials, titanium gypsum contains certain harmful ions, which may cause certain pollution to the surrounding soil and groundwater during long-term service. Therefore, when applied to engineering, titanium gypsum must be cured.

[0005] At present, some research has been carried out on the curing of titanium gypsum for road use, but the following problems still need to be solved. First, the current titanium gypsum curing agent has a complex composition and a wide variety of raw materials, which makes the production process complicated and difficult to prepare on an industrial scale. Second, in order to meet the road performance of titanium gypsum, the current titanium gypsum curing agent dosage is large, and the dosage of some products reaches 20%~40% of the mass of titanium gypsum, which increases the cost of titanium gypsum composite materials as road fillers, and the comprehensive utilization cost is even higher than that of traditional fillers. At the same time, due to the limitations of the material properties of titanium gypsum curing agents, some products must be prepared as separate solutions for incorporation, which changes the traditional roadbed construction method and increases the complexity of the construction of titanium gypsum road composite materials, making it difficult to promote and apply them on a large scale in engineering. Summary of the invention

[0006] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a titanium gypsum curing agent, a preparation method and an application thereof, which can reduce the water absorption and expansion rate of titanium gypsum through the hydration and hardening reaction of the curing agent, while enhancing the mechanical properties and water stability of titanium gypsum, thereby meeting the road performance requirements of titanium gypsum as a roadbed and subbase filler, reducing engineering costs, and simplifying the preparation of the curing agent and the construction process of titanium gypsum.

[0007] In order to achieve the above object, the technical solution of the present invention is: In a first aspect of the present invention, a titanium gypsum curing agent is provided, wherein the raw materials include, by weight: 30 to 50 parts of an activator, 10 to 15 parts of a filler material, 30 to 50 parts of an active solid waste material, 1 to 10 parts of calcium oxide, and 2 to 5 parts of a dispersant; The activator includes agent A and agent B with a mass ratio of 0.025-0.08; the agent A includes sodium hydroxide and potassium hydroxide with a mass ratio of (0.6-1): (0-0.4); the agent B includes ordinary silicate cement and composite silicate cement with a mass ratio of (0.7-1): (0-0.3).

[0008] The second aspect of the present invention provides a method for preparing the titanium gypsum curing agent, comprising the steps of: S11, mixing and grinding the raw materials of the activator A and B to obtain activator powder; S12, grinding the filling material to obtain filling powder; S13, mixing the activator powder, the filler powder, the active solid waste powder, the calcium oxide and the dispersant to obtain the titanium gypsum curing agent.

[0009] The third aspect of the present invention provides an application of the titanium gypsum curing agent, including an application in the preparation of a titanium gypsum roadbed, wherein the titanium gypsum roadbed comprises titanium gypsum and the titanium gypsum curing agent, and the titanium gypsum curing agent accounts for 3-5% of the dry mass of the titanium gypsum.

[0010] In the above application, the method for preparing the titanium gypsum roadbed comprises the steps of: S21, after spreading titanium gypsum with a moisture content of 20-27%, spreading the titanium gypsum curing agent at a ratio of 3-5% of the dry mass of the titanium gypsum; S22, mixing the titanium gypsum and the titanium gypsum curing agent and compacting them; S23. Keep moist and healthy for 3 to 4 days.

[0011] The beneficial effects of the present invention are as follows: 1. The titanium gypsum curing agent provided by the present invention makes full use of the synergistic hydration and hardening effect between various solid waste raw materials. Through the complex salt effect and the tetracoordinate isomorphism effect of silicon, various solid waste raw materials can synergistically activate with titanium gypsum to form compounds or solid solutions with certain strength and stability, and physically encapsulate harmful substances in the titanium gypsum, thereby achieving effective curing of harmful substances in the titanium gypsum and producing a certain road strength; the solid waste-based cementitious material particles reduce the porosity of the titanium gypsum through the filling effect and the generation of more stable compounds or solid solutions, thereby limiting its volume expansion; the solid waste-based cementitious material generates stable compounds through physical densification and filling, reduces porosity, enhances integrity and interfacial adhesion, and hinders water penetration, thereby improving water stability, meeting road performance requirements, and reducing road costs; the raw materials of the curing agent are all common bulk solid waste materials and engineering materials, and only require mixing, homogenization and grinding, and the preparation method is simple.

[0012] 2. The dosage of the titanium gypsum curing agent of the present invention is basically the same as that of the commonly used stabilizer for roads. Compared with the existing curing agent, the dosage is lower, and the total cost of the project can be significantly reduced compared with the traditional fill roadbed, with obvious economic advantages.

[0013] 3. The construction process of the titanium gypsum roadbed and subbase of the present invention is the same as that of the traditional fill roadbed and subbase, and there is no need to modify the existing equipment, and the construction process is simple. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the embodiments.

[0015] A titanium gypsum curing agent, comprising the following components in parts by weight: 30-50 parts of an activator, 10-15 parts of a filler material, 30-50 parts of an active solid waste material, 1-10 parts of calcium oxide, and 2-5 parts of a dispersant; The activator includes agent A and agent B in a mass ratio of (0.025-0.08):1; the agent A includes sodium hydroxide and potassium hydroxide in a mass ratio of (0.6-1):(0-0.4); the agent B includes ordinary silicate cement and composite silicate cement in a mass ratio of (0.7-1):(0-0.3).

[0016] Among the above ingredients, the activator A can provide a strong alkaline environment, promote the breaking and reorganization of the silicon-oxygen bonds and aluminum-oxygen bonds of the active solid waste materials, form a material with hardening properties, and provide a certain strength; in agent B, tricalcium aluminate will react with titanium gypsum to form calcium aluminate (AFt), and provide more hydration products, which are interwoven to form a network structure, wrapping the cementitious material particles and making the structure denser; among them, ordinary silicate cement is a necessary activator, and composite silicate cement is a supplementary activator; in occasions where the requirements for strength and durability are relatively low, composite silicate cement can be used to control costs.

[0017] Optionally, the filling material includes waste glass powder and decarbonized coal gangue in a mass ratio of (0.4~1): (0~0.6), and the filling material is used to fill the tiny gaps inside the titanium gypsum, improve the compactness, reduce the water absorption of the material, and improve the water stability.

[0018] Optionally, the specific surface area of ​​the filler material is 500m 2 / kg and above, so that it can fill into small-sized pores and have a certain potential pozzolanic activity, increase density, and thus reduce water absorption and improve water stability.

[0019] Optionally, the active solid waste material includes blast furnace slag, active steel slag and rice husk ash in a mass ratio of (0.5-1): (0-0.5): (0.5-0.8), and the fineness of each active solid waste material is above 200 mesh; the blast furnace slag powder is S95 base or S105 grade; under alkaline conditions, the sulfate ion (SO4² - ) and calcium ions (Ca² + ) reacts with aluminates to form ettringite (AFt); the hydrated calcium silicate gel, calcium hydroxide and other products generated by the active solid waste materials in an alkaline environment are intertwined with the hydration products of titanium gypsum (such as hemihydrate gypsum) to form a dense network structure, which can absorb the expansion components of titanium gypsum and produce water hardness at the same time, form a certain strength, realize the solidification of multiple components in titanium gypsum, and reduce the leaching of harmful substances; at the same time, it can also react with iron oxides and other substances in titanium gypsum to form hydrated calcium aluminoferrate, further improving the water hardness.

[0020] Optionally, the calcium oxide is a powder material with a fineness of more than 200 meshes, which is used to provide an alkaline environment to assist the activator in jointly activating the silicon aluminum oxides in the active solid waste, destroying the chemical bonds therein, releasing active ions, and promoting the reaction between these ions to form new chemical bonds and gel structures.

[0021] Optionally, the dispersant includes: a mixture of polyvinyl alcohol powder material, triisopropanolamine, and calcium sulfate whiskers in a mass ratio of (0.2~1): (0.2~0.8): (0.5~1); the hydroxyl groups on the molecular chain of the polyvinyl alcohol powder material can form hydrogen bonds with water molecules, thereby enhancing hydrophilicity and water solubility, so that the raw materials of the titanium gypsum curing agent can fully react and further enhance the curing effect of the titanium gypsum; the triisopropanolamine can accelerate the formation of hydration products, thereby improving the strength of the titanium gypsum; the calcium sulfate whiskers can act as a skeleton in the titanium gypsum like fibers, effectively transfer stress, prevent cracks in the titanium gypsum from expanding, and effectively solidify the titanium gypsum.

[0022] The preparation method of the titanium gypsum curing agent comprises the steps of: S11, mixing and grinding the raw materials of the activator A and B to obtain activator powder; S12, grinding the filling material to obtain filling powder; S13, mixing the activator powder, the filler powder, the active solid waste powder, the calcium oxide and the dispersant to obtain the titanium gypsum curing agent.

[0023] In the above steps, step S11 is to fully mix the chemical stimulant A and the mineral phase stimulant B to provide a sufficient strong alkaline environment for the active solid waste material; step S12 is to fully grind the filling material with potential activity to make it have a larger specific surface area, which is conducive to the filling effect and potential volcanic ash activity; the purpose of mixing in step S13 is to prevent the organic chemical substances in the dispersant from being damaged and losing their activity due to the external force of grinding.

[0024] Optionally, the grinding method in S11 is ball milling at a speed of 120-140 rpm for 3-5 minutes until the material passes through a 200-mesh sieve and the dispersion uniformity of the material is above 99%; the grinding method in S12 is ball milling for no less than 5 minutes until the specific surface area is 500m 2 / kg or more; the mixing time of each material in S13 in the high-efficiency powder mixer is not less than 4min.

[0025] The prepared titanium gypsum curing agent can be applied to titanium gypsum roadbed.

[0026] The application of the titanium gypsum curing agent includes the application in the preparation of titanium gypsum roadbed, the titanium gypsum roadbed includes titanium gypsum and the titanium gypsum curing agent, and the titanium gypsum curing agent accounts for 3-5% of the dry mass of the titanium gypsum.

[0027] In the above application, the method for preparing the titanium gypsum roadbed comprises the steps of: S21, after spreading titanium gypsum with a moisture content of 20-27%, spreading the titanium gypsum curing agent at a ratio of 3-5% of the dry mass of the titanium gypsum; S22, mixing the titanium gypsum and the titanium gypsum curing agent and compacting them; S23. Keep moist and healthy for 3 to 4 days.

[0028] In the above process, after the titanium gypsum with a set water content is mixed with the titanium gypsum curing agent, the water contained in the titanium gypsum itself participates in the reaction to achieve water hardness, and gradually stabilizes in the subsequent reaction process to form a dense roadbed.

[0029] Optionally, in S22, titanium gypsum and titanium gypsum curing agent are mixed evenly with a road mixer, rolled 2 to 3 times with a bulldozer, leveled with a leveler, and then compacted to a set compaction degree with a roller, which is the same as a conventional roadbed construction method.

[0030] Optionally, in S23, the geotextile is covered and watered for curing, during which the surface of the geotextile is kept moist to ensure a stable curing process and avoid defects such as cracking.

[0031] In the following examples and comparative examples, the titanium gypsum has the same source, and has the same physical properties and chemical composition.

[0032] Example 1 A titanium gypsum curing agent, comprising the following components in parts by weight: 40 parts of an activator, 12 parts of a filler material, 40 parts of an active solid waste material, 5 parts of calcium oxide, and 2 parts of a dispersant; The activator includes agent A and agent B with a mass ratio of 0.05; agent A is sodium hydroxide, and agent B is P•O 42.5 ordinary Portland cement.

[0033] The filling material is waste glass powder, and the specific surface area of ​​the filling material is 620m 2 / kg.

[0034] The active solid waste materials include blast furnace slag, active steel slag and rice husk ash in a mass ratio of 0.5:0.2:08; the blast furnace slag powder is grade S95.

[0035] Calcium oxide is a powder material with a fineness of more than 200 meshes.

[0036] The dispersant is polyvinyl alcohol powder material, triisopropanolamine and calcium sulfate whisker in a mass ratio of 0.2:0.2:0.5.

[0037] The preparation method of the titanium gypsum curing agent in this embodiment comprises the steps of: S11, putting the A agent and the B agent of the activator into a ball mill according to the set mass ratio and grinding for 3 minutes, the speed of the ball mill is 120rpm, and the dispersion uniformity of the mixture is 99.5%, to obtain the primary mixture of the activator; S12, grind the filler material for 5 minutes to obtain an ultrafine filler material with a specific surface area of ​​620m 2 / kg; S13, the primary mixture of the activator, the ultrafine filler material, the active solid waste powder, the calcium oxide and the dispersant are placed in a high-efficiency powder mixer according to a set ratio and mixed for 4 minutes to form a titanium gypsum curing agent.

[0038] The titanium gypsum curing agent in this embodiment is mixed with titanium gypsum (the titanium gypsum curing agent is 3% of the dry mass of titanium gypsum) to prepare laboratory specimens, including: 50mm×50mm cylindrical specimens, which are cured under standard curing conditions and tested for 3d and 7d laboratory unconfined compressive strength; 200mm×50mm×50mm rectangular specimens are prepared and cured under standard curing conditions to test shrinkage strain; 120mm×120mm cylindrical specimens are tested for stable water immersion expansion rate.

[0039] The titanium gypsum curing agent in this embodiment is mixed with titanium gypsum (the titanium gypsum curing agent is 3% of the dry mass of titanium gypsum), and a leaching toxicity determination test is carried out according to the "Determination Method for Leaching Toxicity of Solid Waste" (GB / T 15555). The indicators measured in the leaching toxicity test include: heavy metal elements such as cadmium, mercury, arsenic, chromium, and sulfides.

[0040] The titanium gypsum curing agent obtained in this embodiment is mixed with titanium gypsum to prepare a titanium gypsum roadbed, comprising the steps of: S21, pre-precipitate the titanium gypsum after filter pressing to make the moisture content reach about 23% for standby use; evenly spread the titanium gypsum after precipitation on the construction site, and evenly spread the titanium gypsum curing agent according to 3% of the dry mass of the titanium gypsum; S22. Use a road mixer to evenly mix the titanium gypsum and titanium gypsum curing agent, use a crawler bulldozer to roll them three times, use a grader to scrape them flat, and use a vibratory roller to roll them to a compaction degree of 96% or above; S23. Cover the geotextile and sprinkle water for 3 and 7 days. Keep the surface of the geotextile moist during the curing period. After curing, use a 100mm diameter coring machine to take cores and cut them into 100mm×100mm cylindrical specimens as on-site specimens to test the on-site unconfined compressive strength.

[0041] Example 2 A titanium gypsum curing agent, the raw materials of which include, by weight, 50 parts of an activator, 15 parts of a filling material, 50 parts of an active solid waste material, 1 part of calcium oxide, and 2 parts of a dispersant.

[0042] The activator includes agent A and agent B with a mass ratio of 0.07, agent A is sodium hydroxide, and agent B is P•O42.5 ordinary silicate cement and P•C42.5 composite silicate cement with a mass ratio of 0.7:0.3.

[0043] The filling material is waste glass powder and decarbonized coal gangue, with a mass ratio of 1:0.3. The specific surface area of ​​the filling material is 600m 2 / kg.

[0044] The active solid waste materials are S95 blast furnace slag powder, steel slag powder and rice husk ash in a mass ratio of 0.5:0.5:0.8.

[0045] The fineness of calcium oxide is 200 mesh.

[0046] The dispersant is a polyvinyl alcohol powder material, triisopropanolamine and calcium sulfate whisker in a mass ratio of 1:0.8:0.5. The steps of the preparation method are the same as those in Example 1, except that: In S12, the specific surface area of ​​the ultrafine filler material obtained is 500m 2 / kg.

[0047] The titanium gypsum curing agent in this example was mixed with titanium gypsum (the titanium gypsum curing agent was 4% of the dry mass of titanium gypsum), and the same laboratory specimens as in Example 1 were prepared and tested, and a leaching toxicity determination test was performed.

[0048] The titanium gypsum curing agent obtained in this example was mixed with titanium gypsum to prepare a titanium gypsum roadbed and a field test piece was taken. The method was the same as that in Example 1, except that: In S21, the titanium gypsum curing agent is evenly spread according to 4% of the dry mass of the titanium gypsum.

[0049] Example 3 A titanium gypsum curing agent, the raw materials of which are measured by weight: 45 parts of an activator, 12 parts of a filling material, 45 parts of an active solid waste material, 10 parts of calcium oxide, and 5 parts of a dispersant.

[0050] The activator includes agent A and agent B with a mass ratio of 0.08, agent A is a mixture of sodium hydroxide and potassium hydroxide with a mass ratio of 0.6:0.4, and agent B is a mixture of P•O42.5 ordinary silicate cement and P•C42.5 composite silicate cement with a mass ratio of 0.9:0.1.

[0051] The filling material is waste glass powder and decarbonized coal gangue, with a mass ratio of 0.5:0.6. The specific surface area of ​​the filling material is 550m 2 / kg.

[0052] The active solid waste materials are S105 blast furnace slag powder, steel slag powder and rice husk ash in a mass ratio of 1:0.5:0.8.

[0053] The fineness of calcium oxide is 200 mesh.

[0054] The dispersant is polyvinyl alcohol powder material, triisopropanolamine and calcium sulfate whisker in a mass ratio of 0.5:0.6:0.8.

[0055] The steps of the preparation method are the same as those in Example 1, except that: In S12, the specific surface area of ​​the ultrafine filler material obtained is 680m 2 / kg.

[0056] The titanium gypsum curing agent in this example was mixed with titanium gypsum (the titanium gypsum curing agent was 5% of the dry mass of titanium gypsum), and the same laboratory specimens as in Example 1 were prepared and tested, and a leaching toxicity determination test was performed.

[0057] The titanium gypsum curing agent obtained in this example was mixed with titanium gypsum to prepare a titanium gypsum roadbed and a field test piece was taken. The preparation method was the same as that in Example 1, except that: In S21, the titanium gypsum curing agent is evenly spread according to 5% of the dry mass of the titanium gypsum.

[0058] Comparative Example 1 The titanium gypsum in this comparative example is from the same source as that in Example 1, and no titanium gypsum curing agent is added.

[0059] The laboratory specimens were prepared according to the size of Example 1 using titanium gypsum with a moisture content of about 23% to form 50mm×50mm cylindrical specimens, which were cured under standard curing conditions and tested for 3d and 7d laboratory unconfined compressive strength; 200mm×50mm×50mm rectangular specimens were prepared and cured under standard curing conditions to test shrinkage strain; 120mm×120mm cylindrical specimens were tested for stable water immersion expansion rate; and leaching toxicity determination tests were conducted.

[0060] The method for preparing titanium gypsum roadbed comprises: The titanium gypsum that has been watered to a moisture content of about 23% is evenly spread on the construction site; the titanium gypsum is mixed and crushed with a road mixer, rolled three times with a crawler bulldozer, leveled with a grader, and rolled to the designed compaction degree with a vibrating roller; the geotextile is covered and watered for curing for 3 and 7 days, and the surface of the geotextile is kept moist during the curing period. After curing, a 100mm diameter coring machine is used to coring, and the cores are cut into 100mm×100mm cylindrical specimens for testing the on-site unconfined compressive strength of the on-site specimens.

[0061] Comparative Example 2 In this comparative example, P•O42.5 ordinary Portland cement is used as the titanium gypsum curing agent. 5% of the dry mass of P•O42.5 ordinary Portland cement is mixed with titanium gypsum to prepare laboratory specimens, including: preparing 50mm×50mm cylindrical specimens, curing them under standard curing conditions, and testing the 3d and 7d laboratory unconfined compressive strength; preparing 200mm×50mm×50mm rectangular specimens, curing them under standard curing conditions, and testing the shrinkage strain; testing the stable water immersion expansion rate with 120mm×120mm cylindrical specimens; and conducting leaching toxicity determination tests.

[0062] The method of preparing titanium gypsum roadbed and taking field test pieces is the same as that in Example 1.

[0063] The properties of the laboratory specimens and field specimens obtained in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are shown in Table 1.

[0064] Table 1 Test results of laboratory specimens and field specimens

[0065] As shown in Table 1, compared with Comparative Examples 1 and 2, the 3d and 7d unconfined compressive strengths of titanium gypsum stabilized by curing agents in laboratory and field tests are greatly improved, which indicates that multi-source solid waste has a synergistic hydration hardening effect, and multi-source solid waste curing agents are suitable for titanium gypsum curing. Through the double salt effect and the tetracoordinate isomorphism effect of silicon, each solid waste raw material can synergistically activate with titanium gypsum, stimulate the active SiO2 and active Al2O3 in the curing agent to generate CSH and CAH gels, and can also react with CAH to generate calcium sulfonate, forming a compound or solid solution with certain strength and stability, physically encapsulating the harmful substances in the titanium gypsum, achieving effective curing of the harmful substances in the titanium gypsum, and producing a certain road strength. At the same time, compared with Comparative Examples 1 and 2, the stable expansion rate and shrinkage rate of titanium gypsum stabilized by curing agents are reduced, and the solid waste-based gelling material particles can effectively reduce the pore space in the titanium gypsum through its filling effect and promote the formation of more stable compounds or solid solutions, thereby inhibiting its excessive expansion. In addition, these solid waste-based cementitious materials also use physical densification and filling mechanisms to further reduce porosity, enhance the overall structural strength of the material and the bonding ability between interfaces, and effectively hinder the penetration of water, thereby improving the water stability of the material and ensuring that it meets the performance standards for road use.

[0066] According to the "Solid Waste Leaching Toxicity Determination Method" (GB / T 15555), the curing agent stabilized titanium gypsum leaching toxicity determination test was carried out on Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, respectively. The indicators measured in the leaching toxicity test include: heavy metal elements such as cadmium, mercury, arsenic, chromium, and sulfides. The results obtained are shown in Table 2.

[0067] Table 2 Results of leaching toxicity test

[0068] It can be seen from Table 2 that the indicators measured in the toxicity determination test of the curing agent-stabilized titanium gypsum heavy metal leachate of Example 1, Example 2 and Example 3 all meet the Class III maximum allowable emission value requirements in GB / T 14848-2017 "Groundwater Quality Standard" and can meet the limit requirements, while Comparative Example 1 and Comparative Example 2 do not meet the limit requirements, indicating that the present invention can achieve effective solidification of harmful substances in titanium gypsum.

[0069] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A titanium gypsum curing agent, characterized in that: In terms of weight, the raw materials include: 30-50 parts of activator, 10-15 parts of filler, 30-50 parts of active solid waste material, 1-10 parts of calcium oxide, and 2-5 parts of dispersant; the activator includes agent A and agent B with a mass ratio of 0.025-0.08; the agent A includes sodium hydroxide and potassium hydroxide with a mass ratio of (0.6-1): (0-0.4); the agent B includes composite silicate cement and ordinary silicate cement with a mass ratio of (0.7-1): (0-0.3).

2. The titanium gypsum curing agent according to claim 1, characterized in that: The filler material includes waste glass powder and decarbonized coal gangue in a mass ratio of (0.4-1): (0-0.6); the specific surface area of ​​the filler material is 500m 2 / kg and above.

3. The titanium gypsum curing agent according to claim 1, characterized in that: The active solid waste materials include blast furnace slag, active steel slag and rice husk ash in a mass ratio of (0.5-1): (0-0.5): (0.5-0.8).

4. The titanium gypsum curing agent according to claim 1, characterized in that: The dispersant comprises a mixture of polyvinyl alcohol powder material, triisopropanolamine and calcium sulfate whiskers in a mass ratio of (0.2-1): (0.2-0.8): (0.5-1).

5. A method for preparing the titanium gypsum curing agent according to any one of claims 1 to 4, characterized in that: Includes steps: S11, mixing and grinding the raw materials of the activator A and B to obtain activator powder; S12, grinding the filling material to obtain filling powder; S13, mixing the activator powder, the filler powder, the active solid waste powder, the calcium oxide and the dispersant to obtain the titanium gypsum curing agent.

6. The method for preparing the titanium gypsum curing agent according to claim 5, characterized in that: The grinding method in S11 is to pass through a 200-mesh screen, and the uniformity of the dispersion of the material is above 99%; the grinding method in S12 is ball milling to a specific surface area of ​​500m 2 / kg or more.

7. An application of the titanium gypsum curing agent as claimed in any one of claims 1 to 4, characterized in that: The invention comprises application in preparing titanium gypsum roadbed, wherein the titanium gypsum roadbed comprises titanium gypsum and the titanium gypsum curing agent, and the titanium gypsum curing agent accounts for 3-5% of the dry mass of the titanium gypsum.

8. The use of the titanium gypsum curing agent as claimed in claim 7, characterized in that: The preparation method of the titanium gypsum roadbed comprises the steps of: S21, after spreading titanium gypsum with a moisture content of 20-27%, spreading the titanium gypsum curing agent at a ratio of 3-5% of the dry mass of the titanium gypsum; S22, mixing the titanium gypsum and the titanium gypsum curing agent and compacting them; S23. Keep moist and healthy for 3 to 4 days.

9. The use of the titanium gypsum curing agent as claimed in claim 8, characterized in that: In S22, titanium gypsum and titanium gypsum curing agent are mixed evenly with a road mixer, rolled 2 to 3 times with a bulldozer, leveled with a leveler, and then compacted to a set compaction degree with a roller.

10. The use of the titanium gypsum curing agent according to claim 8, characterized in that: In S23, the geotextile is covered and watered to maintain curing, and the surface of the geotextile is kept moist during the curing process.

Citation Information

Patent Citations

  • Curing agent for titanium gypsum road and preparation method and application method of curing agent

    CN110668777A

  • Method for manufacturing roadbed base layer and subbase layer material by using titanium gypsum

    CN114933462A

  • Titanium gypsum curing material and environmental risk assessment method thereof

    CN119038902A

  • Calcium oxide solidifier composition comprisingtitanium gypsum

    KR100516188B1

Cited By

  • Titanium gypsum composite roadbed applied to expressway and construction method

    CN120943574A